"Betwixt this World and that of Grace": Calvinism and the Tortured Self - Harmelen, Boehm Van Rachel (My University, 1992)
This study attempts to understand the origin and outcome of the contradiction that is present throughout much of George Herbert's 2'1le Temple. The roots of this contradiction will be examined from the perspective of John Calvin's theology of grace. The doctrine of grace, from the Calvin's point of view, includes both an emphasis on the necessity and the ineffectuality of works for salvation. Herbert, like Calvin, was keenly aware of the difficulty of struggling between these opposing notions of grace and works. Hence, he experienced this contradiction as the "affliction" of his daily life, an affliction embodied in many of the poems throughout Tbe Temple.
In seeking the origins of this contradiction in Herbert, we will look to his poetry, the Bible, as well as the works of John Calvin. An examination of the Church of England in Herbert's day and how it interpreted the doctrine of grace will add to our knowledge of how to read grace in 2'1le Temple. Having clearly defined contradiction in Herbert and how it relates to grace as he perceived it, the study will proceed to examine a number of poems specifically for the struggles they portray between the opposing notions of grace and works.
Keywords: English Language and Literature; English Language and Literature